Design Of Multi-Family Product Platform By Using Modularity Approach - A. B. Abdullah, A. B. Abdullah; A. R. Kamaruddin , A. R. Kamaruddin; Z. M. Ripin, Z. M. Ripin (Penerbit UTM Press, 2005)

(untitled)
Design for modularity is one of the best design technique as it promotes better and faster designing process. Due to functional independence and physical similarities, it tends to drive for better platform development. This paper discusses the application of modularity approach to design platform from multi-family product. By utilizing the conventional heuristics rules to identify modules, a platform is then developed so that it can be shared among products. Three consumer products from different family were used as case study. As a result, new designs were proposed that depicted several improvements to the products.